Bread matters: A national initiative to profile the genetic diversity of Australian wheat - Edwards, D.; Wilcox, S.; Barrero, R.; Fleury, D.; Cavanagh, C.; Forrest, K.; Hayden, M.; Moolhuijzen, Paula; Keeble-Gagnère, G.; Bellgard, M.; Lorenc, M.; Shang, C.; et al. (2012)
The large and complex genome of wheat makes genetic and genomic analysis in this important species both expensive and resource intensive. The application of next-generation sequencing technologies is particularly resource intensive, with at least 17Gbp of sequence data required to obtain minimal (1×) coverage of the genome. A similar volume of data would represent almost 40× coverage of the rice genome. Progress can be made through the establishment of consortia to produce shared genomic resources. Australian wheat genome researchers, working with Bioplatforms Australia, have collaborated in a national initiative to establish a genetic diversity dataset representing Australian wheat germplasm based on whole genome next-generation sequencing data. Here, we describe the establishment and validation of this resource which can provide a model for broader international initiatives for the analysis of large and complex genomes.